2015
DOI: 10.3109/08982104.2015.1019515
|View full text |Cite
|
Sign up to set email alerts
|

The influence of bile salts on the response of liposomes to ultrasound

Abstract: Bile salts may be used to increase or decrease the sensitivity of liposomes to low frequency ultrasound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…While extrusion generates shear forces that cause disruption of the lipid, Triton X is a non‐ionic surfactant that is commonly applied to disrupt lipid membranes . Of the 2 treatments, extrusion caused the greater increase in fluorescence compared to Triton X.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While extrusion generates shear forces that cause disruption of the lipid, Triton X is a non‐ionic surfactant that is commonly applied to disrupt lipid membranes . Of the 2 treatments, extrusion caused the greater increase in fluorescence compared to Triton X.…”
Section: Discussionmentioning
confidence: 99%
“…Liposomes were prepared using the thin film hydration method as described in an earlier publication . Lipid composition for liposomes included DSPC:Chol (87‐13 mol %) and DOPE:DSPC:Chol (30‐57‐13 mol %).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…They also found that liposomes made of taurocholate and DOPE showed less sensitivity to high frequency US than liposomes containing only DOPE. It was speculated that this phenomenon was because of a preferred shape arising from the combination of taurocholate and DOPE in the phospholipid bilayer [174].…”
Section: Ultrasound-responsivementioning
confidence: 99%